An all-solid-state hydrogen negative ion battery and a preparation method thereof

CN119725793BActive Publication Date: 2026-10-23DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311272077.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2026-10-23
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

但目前尚无可以实现循环充放电的氢负离子电池的报道

Benefits of technology

本申请所提供的氢负离子二次电池可以在室温及较宽温度下运行,可以实现多次循环充放电,该新型电池有望应用于实际生活和生产中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725793B_ABST
    Figure CN119725793B_ABST
Patent Text Reader

Abstract

The application discloses a kind of all-solid-state hydrogen negative ion battery and preparation method, the all-solid-state hydrogen negative ion battery includes in turn from positive electrode to negative electrode direction: positive electrode current collector, positive electrode active layer, hydrogen negative ion electrolyte layer, negative electrode active layer and negative electrode current collector;The hydrogen negative ion electrolyte layer is the hydride containing rare earth metal element.The negative electrode active material layer contains metal or low hydrogen content hydride, and the positive electrode active material layer contains high hydrogen content hydride, and the solid electrolyte layer conducts hydrogen negative ion.The application can be charged and discharged as a new hydrogen negative ion battery, with good cycle performance, greatly widen the research system of secondary battery, with far-reaching application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to an all-solid-state hydrogen negative ion battery and its preparation method, belonging to the field of clean energy technology. Background Technology

[0002] Energy's immense role in promoting human society has long made it an essential condition for technological progress and social development. Energy storage technology, as a crucial link in the efficient utilization of energy, is of paramount importance. Secondary batteries, with their advantages of high efficiency, safety, environmental friendliness, high energy density, and high recyclability, have become the preferred choice for energy storage devices. Currently, secondary batteries have evolved into lead-acid batteries, nickel-metal hydride batteries, lithium batteries, as well as flow batteries, sodium batteries, and magnesium batteries. Limited by material properties, various electrochemical energy storage devices have their own applicable scenarios. Developing entirely new battery systems can significantly broaden the application scope of electrochemical energy storage.

[0003] When hydrogen forms compounds, it can easily lose an electron to become a proton, or it can gain an electron to become a hydride ion. H - The ion has a larger radius, similar to F. - O 2- While similar in appearance, it contains only one valence charge, resulting in a lower charge density and easier polarization. This differs significantly from proton conduction in materials, where protons have a high charge density and are often strongly bonded to oxygen in oxides, leading to high activation energies. Furthermore, the standard redox potential of hydride anions is -2.3 V, close to that of magnesium ions (-2.4 V), but its atomic mass is only 1 / 24 that of magnesium. This makes it a promising candidate for a new generation of high-energy-density, high-potential ion conductor materials in batteries. Research on H... - The rapid conduction of ions, when applied to batteries, holds promise for revolutionizing electrochemical energy storage technology.

[0004] Several potential ionic conductors that can be used as electrolytes in hydrogen anion batteries have been reported, mainly falling into two categories: one is alkaline earth metal-based, including binary hydrides, oxyhydrides, and halide hydrides; the other is rare earth metal-based, mainly oxyhydrides and pure rare earth metal hydrides. However, there are currently no reports of hydrogen anion batteries that can achieve cyclic charging and discharging. Summary of the Invention

[0005] The all-solid-state hydrogen negative ion battery disclosed in this application can achieve reversible charge-discharge at room temperature. As a novel electrochemical energy storage device, this invention will broaden the research system of electrochemical energy storage and has great application value.

[0006] This invention discloses a novel rechargeable hydrogen negative ion all-solid-state battery. Specifically, the hydrogen negative ion all-solid-state battery includes a positive electrode current collector, a positive electrode active material layer, a hydrogen negative ion solid electrolyte, a negative electrode active material layer, and a negative electrode current collector; the negative electrode active material layer contains a metal or a low-hydrogen metal hydride, the positive electrode active material layer contains a high-hydrogen metal hydride, and the solid electrolyte layer conducts hydrogen negative ions.

[0007] According to one aspect of this application, an all-solid-state hydrogen negative ion battery is provided, wherein the all-solid-state hydrogen negative ion battery comprises, in sequence from the positive electrode to the negative electrode: a positive electrode current collector, a positive electrode active layer, a hydrogen negative ion electrolyte layer, a negative electrode active layer, and a negative electrode current collector. The hydrogen anion electrolyte layer is a hydride containing rare earth metal elements. The all-solid-state hydrogen negative ion battery is a rechargeable battery.

[0008] Optionally, the all-solid-state hydrogen ion battery utilizes hydrogen ions (H+) to... - The migration of hydrogen ions enables charging and discharging; the hydrogen ion solid electrolyte is used inside the battery to conduct hydrogen ions (H+). - ).

[0009] Optionally, the rare earth metal element includes at least one selected from scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium.

[0010] Optionally, the selected hydrogen anion electrolyte layer is selected from rare earth metal hydrides or partially contains rare earth metal hydrides; Rare earth metals include at least one of scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb), and lutetium (Lu).

[0011] Optionally, the thickness of the hydrogen anion electrolyte layer is 0.1 μm to 10 mm.

[0012] Optionally, the thickness of the hydrogen anion electrolyte layer is independently selected from any value among 0.1um, 0.2um, 0.5um, 1um, 10um, 100um, 1mm, 5mm, and 10mm, or a range between any two of the above.

[0013] Optionally, the thicknesses of the positive electrode active layer and the negative electrode active layer are independently selected from 0.2 μm to 1 mm.

[0014] Optionally, the thickness of the positive electrode active layer and the negative electrode active layer are independently selected from any value of 0.2um, 0.5um, 1um, 10um, 100um, 1mm or a range between any two of the above.

[0015] Optionally, the negative electrode active layer comprises one of group IA, IIA, IIIB, IVB, and VB metals.

[0016] Optionally, the metal of the negative electrode active layer is a group I or II metal or a group III, IV or V metal or its alloy.

[0017] Optionally, the negative electrode active layer comprises a metal or a hydride with a low hydrogen content.

[0018] Optionally, the positive electrode active material layer contains hydrides with a high hydrogen content.

[0019] Optionally, the negative electrode active layer comprises a metal or a low-hydrogen metal hydride, wherein the hydrogen content of the low-hydrogen metal hydride is 0-50% of that in a saturated hydrogenated state.

[0020] Optionally, the positive electrode active material includes a high-hydrogen-content metal hydride, wherein the hydrogen content of the high-hydrogen-content metal hydride is 50-100% of that in a saturated hydrogenated state, and the relative hydrogen content of the selected low-hydrogen-content hydride is lower than that of the high-hydrogen-content metal hydride.

[0021] Optionally, the metal in the low-hydrogen-content metal hydride and the high-hydrogen-content metal hydride is independently selected from one of Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Pd, and Al.

[0022] Optionally, the positive current collector and the negative current collector are independently selected from at least one of gold, silver, copper, palladium, platinum, iron, titanium, cobalt, nickel, and aluminum.

[0023] According to another aspect of this application, a method for preparing the all-solid-state hydrogen negative ion battery described above is provided, wherein the positive electrode active layer, the hydrogen negative ion electrolyte layer and the negative electrode active layer are prepared by one of the following methods: layer pressing molding, integral pressing molding or physical deposition molding, and then assembled to obtain the all-solid-state hydrogen negative ion battery.

[0024] Optionally, the layered pressing method includes pressing the positive electrode active layer, the hydrogen anion electrolyte layer and the negative electrode active layer into shape respectively.

[0025] Preferably, the "layer pressing" conditions are as follows: at 1~100 MPa, the solid electrolyte is pressed into shape separately, the positive and negative electrodes are pressed into shape separately, and the formed positive and negative electrodes and electrolyte are polished and then stacked and pressed to form a battery.

[0026] Optionally, the pressure for compression molding is 1~100 MPa.

[0027] Optionally, the pressing pressure is independently selected from any value of 1 MPa, 5 MPa, 10 MPa, 20 MPa, 50 MPa, 80 MPa, 100 MPa or a range between any two of the above.

[0028] Optionally, the pressing and molding time is 0.5 to 1 hour.

[0029] Optionally, the pressing time is independently selected from any value of 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h or a range between any two of the above.

[0030] Optionally, the integral pressing method includes: integrally pressing the positive electrode active layer, the hydrogen negative ion electrolyte layer, and the negative electrode active layer.

[0031] Preferably, "integrated compression" involves feeding all the raw material powders of all components into a tablet press in sequence and pressing them at 1~100 MPa, and optionally increasing the pressure holding time as needed, for a time of 0.1~4 h, preferably 0.5-1 h.

[0032] Optionally, the pressure for integral pressing is 1~100 MPa.

[0033] Optionally, the pressure for integral pressing is independently selected from any value of 1 MPa, 5 MPa, 10 MPa, 20 MPa, 50 MPa, 80 MPa, 100 MPa or a range between any two of the above.

[0034] Optionally, the integral pressing time is 0.1 to 4 hours.

[0035] Optionally, the integral pressing time is independently selected from any value of 0.1h, 0.5h, 1h, 2h, 3h, 4h or a range between any two of the above.

[0036] Optionally, the integral pressing time is 0.5~1h.

[0037] Optionally, the physical deposition method is selected from at least one of electron beam evaporation, laser evaporation, sputtering, and laser pulse.

[0038] According to another aspect of this application, an application of the above-described all-solid-state hydrogen negative ion battery in energy storage is provided.

[0039] The beneficial effects that this application can produce include: The hydrogen negative ion secondary battery provided in this application can operate at room temperature and a wide temperature range, and can achieve multiple charge-discharge cycles. This new type of battery is expected to be applied in real life and production.

[0040] The novel hydrogen negative ion battery provided in this application can achieve charging and discharging, has good cycle performance, greatly expands the research system of secondary batteries, and has profound application value. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of the battery structure constructed in Embodiment 1 of this application.

[0042] Figure 2 The charging and discharging curves of the LaH2 / LaH3-BaH2 / LaH3 battery under different current densities in Example 2 of this application are shown.

[0043] Figure 3 The above shows the reversible charge-discharge curves of the CeH2 / CeH3-SrH2 / CeH3 battery in Example 3 of this application after more than 20 cycles. Detailed Implementation

[0044] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0045] Unless otherwise specified, all raw materials used in the embodiments of this application were purchased through commercial channels.

[0046] Example 1: All-solid-state hydrogen negative ion battery like Figure 1 As shown, the all-solid-state hydrogen ion battery, from positive to negative electrode, comprises: a positive electrode current collector, a positive electrode active layer, a hydrogen ion electrolyte layer, a negative electrode active layer, and a negative electrode current collector; the hydrogen ion electrolyte layer is a hydride containing rare earth metal elements. The negative electrode active material layer contains metals or low-hydrogen hydrides, the positive electrode active material layer contains high-hydrogen hydrides, and the solid electrolyte layer conducts hydrogen ions. The all-solid-state hydrogen ion battery utilizes hydrogen ions (H+) to conduct hydrogen ions. - The migration of hydrogen ions enables charging and discharging; the hydrogen ion solid electrolyte is used inside the battery to conduct hydrogen ions (H+). - ).

[0047] Example 2: Construction of LaH2 / LaH3-BaH2 / LaH3 battery (1) Weigh 50 mg LaH2, 90 mg LaH3-BaH2 composite electrolyte and 50 mg LaH3 in the glove box, and put them into the mold in order. Use a hydraulic press to press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm, with a pressure of 100 MPa. (2) The prepared sheet is loaded into a stainless steel battery clip. Nickel foam is used as a current collector on both sides of the sheet to increase the contact area and reduce the contact resistance. (3) The electrochemical performance of the battery was tested using an electrochemical workstation. A schematic diagram of the battery structure is shown below. Figure 1 As shown, the charge-discharge curves at different current densities are as follows: Figure 2 As shown, from Figure 2 As can be seen, this battery can be charged and discharged at different current densities, with a capacity as high as 300 mA hg. -1 .

[0048] Example 3: Construction of CeH2 / CeH3-SrH2 / CeH3 battery (1) Weigh 50 mg CeH2, 90 mg CeH3-SrH2 composite electrolyte and 50 mg CeH3 in the glove box, and put them into the mold in order. Use a hydraulic press to press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm, with a pressure of 100 MPa. (2) The prepared sheet is loaded into a stainless steel battery clip. Nickel foam is used as a current collector on both sides of the sheet to increase the contact area and reduce the contact resistance. (3) The electrochemical performance of the battery was tested using an electrochemical workstation. The charge-discharge curves are shown below. Figure 3 As shown, from Figure 3 It can be seen that the secondary battery can achieve more than 20 reversible charge-discharge cycles, and has good cyclic charge-discharge performance.

[0049] Example 4: Constructing PrH 0.1 / LaH x LiAlH4 battery (1) Weigh 1.2 g of LiAlH4 and 1 g of electrolyte powder LaH into the glove box. x Mix and grind them in a mortar to form the positive electrode; (2) Weigh 1.2 grams of PrH into the glove box. 0.1 1 gram of electrolyte powder LaH x The mixture is ground in a mortar and pestle to serve as the negative electrode. (3) Press the positive and negative electrode powders and electrolyte powders into thin sheets at 100 MPa, maintain the pressure for 0.5 h, polish them, and stack them into a battery in sequence; (4) The stacked solid-state battery was loaded into a stainless steel battery clasp, and copper foam was used as the current collector. The electrochemical performance of the battery was tested using an electrochemical workstation.

[0050] Example 5: Construction of Mg / LaH x / MgH2 battery (1) Weigh 0.25 g of MgH2 and 1 g of electrolyte powder LaH into the glove box. x Mix and grind them in a mortar to form the positive electrode; (2) Weigh 0.25 g of Mg and 1 g of electrolyte powder LaH into the glove box. x The mixture is ground in a mortar and pestle to serve as the negative electrode. (3) Press the positive and negative electrode powders and electrolyte powders into thin sheets at 100 MPa, maintain the pressure for 0.5 h, polish them, and stack them into a battery in sequence; (4) The stacked solid-state battery was loaded into a stainless steel battery clasp, and copper foam was used as the current collector. The electrochemical performance of the battery was tested using an electrochemical workstation.

[0051] Example 6: Construction of Ti / NdH3-Mg3N2 / TiH2 and Study of its Performance (1) Weigh 0.4 g of NdH3-Mg3N2 electrolyte powder in a glove box, and press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa; (2) Using physical deposition, Ti was deposited in situ to a thickness of 1 micrometer. TiH2 was deposited in situ on the other end of the electrolyte to a thickness of 1 micrometer. (3) Use the thin film obtained in step (2) as a battery. Use aluminum foil on both sides of the thin film as current collectors and use an electrochemical workstation to test the battery performance.

[0052] Example 7: Construction of Li / YH3-BaH2 / CaH2 battery (1) Weigh 5 mg Li, 90 mg YH3-BaH2 composite electrolyte and 20 mg CaH2 in the glove box, and put them into the mold in order. Use a hydraulic press to press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm, with a pressure of 100 MPa. (2) The prepared sheet is loaded into a stainless steel battery clip. Nickel foam is used as a current collector on both sides of the sheet to increase the contact area and reduce the contact resistance. (3) Use an electrochemical workstation to test the electrochemical performance of the battery.

[0053] Example 8: Construction of Ce / SmH2-BaO / NaAlH4 battery (1) Weigh 50 mg Ce, 90 mg SmH2-BaO composite electrolyte and 50 mg NaAlH4 in the glove box, and put them into the mold in order. Use a hydraulic press to press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm, with a pressure of 100 MPa. (2) The prepared sheet is loaded into a stainless steel battery clip. Nickel foam is used as a current collector on both sides of the sheet to increase the contact area and reduce the contact resistance. (3) Use an electrochemical workstation to test the electrochemical performance of the battery.

[0054] Example 9: Preparation of Ti / PrH3-MgO / PmH2 and Study of its Properties (1) Weigh 0.4 g of PrH3-MgO electrolyte powder in a glove box, and use a hydraulic press to press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm, at a pressure of 100 MPa; (2) Using a sputtering method, under a hydrogen atmosphere, PmH2 was deposited onto the above electrolyte sheet to a thickness of 1 micrometer. Under an argon atmosphere, Ti was deposited onto the electrolyte to a thickness of 1 micrometer. (3) Use the thin film obtained in step 2 as a battery, and use aluminum foil on both sides of the thin film as current collectors. Use an electrochemical workstation to test the battery performance.

[0055] Example 10: Construction of LaH 2.5 / LaH-NaH / PmH 0.1 Battery (1) Weigh out 50 mg of LaH in the glove box. 2.5 90 mg LaH3-NaH complex electrolyte and 50 mg PmH 0.1 The powder is placed evenly into the mold in sequence, and a hydraulic press is used to press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm, at a pressure of 100 MPa. (2) The prepared sheet is loaded into a stainless steel battery clip. Nickel foam is used as a current collector on both sides of the sheet to increase the contact area and reduce the contact resistance. (3) Use an electrochemical workstation to test the electrochemical performance of the battery.

[0056] Example 11 Preparation of Pd / NdH3-Mg3N2 / PdH 0.6 And study its performance (1) Weigh 0.4 g of NdH3-Mg3N2 electrolyte powder in a glove box, and press the powder into a thin sheet with a diameter of 10 mm and a thickness of about 1 mm using a hydraulic press at a pressure of 100 MPa; (2) Pd was deposited in situ onto the other end of the electrolyte using a vapor deposition method, with a deposition thickness of 0.2 micrometers. In-situ deposition of PdH 0.6 The deposition thickness is 0.2 micrometers; (3) Use the thin film obtained in step (2) as a battery. Use aluminum foil on both sides of the thin film as current collectors and use an electrochemical workstation to test the battery performance.

[0057] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method of using an all-solid-state hydrogen negative ion battery, characterized in that, The all-solid-state hydrogen negative ion battery comprises, from positive to negative, the following components in sequence: positive electrode current collector, positive electrode active layer, hydrogen negative ion electrolyte layer, negative electrode active layer, and negative electrode current collector; The hydrogen anion electrolyte layer is selected from rare earth metal hydrides or contains rare earth metal hydrides. The positive electrode active layer contains a metal hydride with a high hydrogen content, wherein the hydrogen content of the high hydrogen content metal hydride is 50-100% of that in a saturated hydrogenated state; The negative electrode active layer contains a low-hydrogen metal hydride, wherein the hydrogen content of the low-hydrogen metal hydride is 0-50% of that in a saturated hydrogenated state. The relative hydrogen content of the high-hydrogen metal hydride is higher than that of the low-hydrogen metal hydride; The preparation method of the all-solid-state hydrogen negative ion battery is as follows: the positive electrode active layer, the hydrogen negative ion electrolyte layer and the negative electrode active layer are prepared by integral pressing molding, and then assembled to obtain the all-solid-state hydrogen negative ion battery. The all-solid-state hydrogen negative ion battery is used as a rechargeable battery.

2. The method according to claim 1, characterized in that, The rare earth metal elements include at least one of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and lutetium.

3. The method according to claim 1, characterized in that, The thickness of the hydrogen negative ion electrolyte layer is 0.1 μm to 10 mm.

4. The method according to claim 1, characterized in that, The thicknesses of the positive electrode active layer and the negative electrode active layer are independently selected from 0.2µm to 1mm.

5. The method according to claim 1, characterized in that, The negative electrode active layer contains one of the metals of group IA, IIA, IIIB, IVB, and VB.

6. The method according to claim 1, characterized in that, The metals in the low-hydrogen-content metal hydrides and high-hydrogen-content metal hydrides are independently selected from one of the following: Li, Na, K, Rb, Cs, Mg, Ca, Sr, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Pd, and Al.

7. The method according to claim 1, characterized in that, The positive current collector and the negative current collector are independently selected from at least one of gold, silver, copper, palladium, platinum, iron, titanium, cobalt, nickel, and aluminum.

8. The method according to claim 1, characterized in that, The integral pressing molding method includes: pressing the positive electrode active layer, the hydrogen negative ion electrolyte layer, and the negative electrode active layer as an integral unit.

9. The method according to claim 1, characterized in that, The pressure for integral pressing is 1~100MPa.

10. The method according to claim 1, characterized in that, The integral pressing and molding time is 0.1~4h.

11. The method according to claim 1, characterized in that, The integral pressing and molding time is 0.5~1h.